Pengetahuan Mahasiswa teknik informatika Tentang Bahaya Penggunaan Earphone - Lora Marlita; Rahmat Sabani (LPPM Universitas Abdurrab, 2025)
The increasingly widespread use of earphones among students can have a negative impact on hearing health if used for a long time and at high volume. Informatics Engineering students, who often interact with audio technology, are a group at risk of experiencing hearing loss due to unsafe earphone use. This study aims to determine the level of knowledge of Informatics Engineering students at Abdurrab University about the dangers of earphone use in 2025. This study uses a quantitative method with a descriptive approach. The research sample consisted of 87 respondents taken using cluster techniques from a total population of 132 students. Data collection was carried out using a questionnaire, and the data results were analyzed univariately. The results showed that the level of student knowledge about the dangers of earphone use was in the sufficient category for 40 respondents (46%), the good category for 27 respondents (31%), and the poor category for 20 respondents (23%). The conclusion of this study is that the majority of Informatics Engineering students at Abdurrab University have sufficient knowledge about the dangers of earphone use. This indicates the need for further education regarding the safe use of earphones to prevent hearing loss in the future.